2012
DOI: 10.3340/jkns.2012.52.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Meningiomas, WHO Grade Il : Prognostic Implications of Clinicopathologic Features

Abstract: ObjectiveIntracranial meningiomas are primarily benign tumors with a good prognosis. Although WHO grade II meningiomas are rare (2-10%), WHO grade II meningiomas have higher recurrence and mortality rates than benign. We evaluated the patient recurrence rate and investigated the prognostic factors of WHO grade II meningiomas.MethodsBetween 1993 and 2005, 55 patients were diagnosed with WHO grade II meningiomas in our hospital. WHO grade II meningiomas (n=55) were compared with other WHO grades meningiomas (I, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…grade II. MGTR is associated with better local control than incomplete resection [11,[20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…grade II. MGTR is associated with better local control than incomplete resection [11,[20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, recurrence rates vary between studies, depending on both the duration of follow-up and the number of patients studied. An analysis of some of these studies has shown that the patient's age at diagnosis, 20 complete resection or GTR, 30 and postoperative radiotherapy 20,33 are invariably associated with lower risks of atypical meningioma recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Our cases' age range was wide differing from 22 to 75, but mean age was 55.8±50 years and a slight female predominance of 69% was obtained similar with the literature (Greenberg, 2001;Yılmaz, et al, 2012). Moon et al (2012), evaluated prognostic factors of WHO Grade II meningiomas and found out that the patients had a median age of 48.4 years and similar to our study group there has been slight female predominance with 29/26: Female/male in their series. In a study conducted by Mahmood et al (1993), typical and malign meningiomas were observed in males more often than females.…”
Section: Discussionmentioning
confidence: 99%